Application of SolidWorks software in preoperative planning of high tibial osteotomy - Lu, Yufeng; Wang, Xue; Yang, Bo; Xu, Zhaochen; Zhang, Baogang; Jia, Bin; He, Jinlong; Qi, Liang; Wang, Min; Qiao, Feng (Frontiers in Surgery, 2023)
Purpose: Open-wedge high tibial osteotomy (HTO) is a common surgical treatment for medial osteoarthritis in young and active patients. The accuracy of osteotomy is closely associated with postoperative efficacy. The accuracy of digital preoperative planning is higher than that of the preoperative manual measurement and several computer software with varying accuracy and convenience are used for digital preoperative planning. This study aimed to use the SolidWorks software for HTO preoperative planning and to determine its accuracy and reliability in HTO preoperative planning. Methods: We reviewed the data of 28 patients with 54 with medial compartment knee arthritis who underwent open-wedge HTO preoperative planning using SolidWorks between June 2019 and March 2021. The standard anteroposterior standing whole-leg radiographs were assessed before and 6 weeks after the surgery. The correction angle, weight-bearing line (WBL) ratio, mechanical femorotibial angle (mFTA), and medial proximal tibial angle (MPTA) before and after the surgery were compared. The clinical results were evaluated using the Knee Society score. Results: At 6 weeks after the surgery, the WBL ratio was corrected from 16.8% to 50.5%, mFTA was corrected from 6.4° varus to 1.2° valgus, and MPTA was corrected from 83.4° to 89.3°. No significant difference was observed between the predicted correction angle before the surgery and the correction angle measured 6 weeks after the surgery (t = -1.745, p = 0.087). The knee score and function score of Knee Society increased from 76.4 and 80.7 before surgery to 95.0 and 95.7, respectively. Conclusions: The SolidWorks software showed high accuracy and reliability in preoperative planning of open-wedge HTO in patients with medial compartment knee arthritis.